Critical infrastructure protection V 5th IFIP WG 11.10 International Conference on Critical Infrastructure Protection, ICCIP 2011, Hanover, NH, USA, March 23-25, 2011, Revised Selected Papers - IFIP Working Group 11.10 International Conference on Critical Infrastructure Protection 2011 Hanover, New Hampshire); Butts, Jonathan; Shenoi, Sujeet; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
The information infrastructure---comprising computers, embedded devices, networks and software systems---is vital to day-to-day operations in every sector: information and telecommunications, banking and finance, energy, chemicals and hazardous materials, agriculture, food, water, public health, emergency services, transportation, postal and shipping, government and defense. Global business and industry, governments, indeed society itself, cannot function effectively if major components of the critical information infrastructure are degraded, disabled or destroyed. Critical Infrastructure Protection V describes original research results and innovative applications in the interdisciplinary field of critical infrastructure protection. Also, it highlights the importance of weaving science, technology and policy in crafting sophisticated, yet practical, solutions that will help secure information, computer and network assets in the various critical infrastructure sectors. Areas of coverage include: Themes and Issues, Control Systems Security, Infrastructure Security, and Infrastructure Modeling and Simulation. This book is the 5th volume in the annual series produced by the International Federation for Information Processing (IFIP) Working Group 11.10 on Critical Infrastructure Protection, an international community of scientists, engineers, practitioners and policy makers dedicated to advancing research, development and implementation efforts focused on infrastructure protection. The book contains a selection of 14 edited papers from the 5th Annual IFIP WG 11.10 International Conference on Critical Infrastructure Protection, held at Dartmouth College, Hanover, New Hampshire, USA in the spring of 2011. Critical Infrastructure Protection V is an important resource for researchers, faculty members and graduate students, as well as for policy makers, practitioners and other individuals with interests in homeland security. Jonathan Butts is an Assistant Professor of Computer Science at the Air Force Institute of Technology, Wright-Patterson Air Force Base, Ohio, USA. Sujeet Shenoi is the F.P. Walter Professor of Computer Science at the University of Tulsa, Tulsa, Oklahoma, USA.
Electronic reproduction.
Keywords: Computer networks -- Security measures -- Congresses; Computer security -- Congresses; Cyberinfrastructure -- Security measures -- Congresses; Electronic books